Eksplorasi Kebutuhan Teknologi Bagi Penyandang Disabilitas di Belu: Studi Kualitatif untuk Pengembangan Aplikasi Pendukung - Ulu Hale, Yunita Herlinia (Blueprint Journal, 2025)
People with disabilities often face challenges in accessing technology that can support their daily lives. This study aims to explore the technology needs of people with disabilities in Belu, East Nusa Tenggara, with a focus on the development of supporting applications. Through a qualitative approach, this study involved in-depth interviews with people with disabilities, their families, and service providers. The results of the study indicate that there is an urgent need for applications that can facilitate accessibility, communication, and education for people with disabilities. These findings are expected to provide a basis for the development of more inclusive and responsive technology solutions to the needs of the disabled community in Belu.